The effect of the slit configuration on the H2 1-0 s(1) to Br γ line ratio of spatially resolved planetary nebulae. Issue 3 (27th July 2020) - Aleman, Isabel
ABSTRACT: The H2 1-0 S(1)/Br γ ratio ( R (Br γ)) is used in many studies of the molecular content in planetary nebulae (PNe). As these lines are produced in different regions, the slit configuration used in spectroscopic observations may have an important effect on their ratio. In this work, observations and numerical simulations are used to demonstrate and quantify such effect in PNe. The study aims to assist the interpretation of observations and their comparison to models. The analysis shows that observed R (Br γ) ratios reach only values up to 0.3 when the slit encompasses the entire nebula. Values higher than that are only obtained when the slit covers a limited region around the H2 peak emission and the Br γ emission is then minimized. The numerical simulations presented show that, when the effect of the slit configuration is taken into account, photoionization models can reproduce the whole range of observed R (Br γ) in PNe, as well as the behaviour described above. The argument that shocks are needed to explain the higher values of R (Br γ) is thus not valid. Therefore, this ratio is not a good indicator of the H2 excitation mechanism as suggested in the literature.